Association Between Peripheral Blood Monocyte Count and Mucosal Healing in Japanese Patients With Ulcerative Colitis. Issue 11 (18th November 2021) - Furukawa, Shinya; Ikeda, Yoshio; Yagi, Sen; Miyake, Teruki; Shiraishi, Kana; Tange, Kazuhiro; Hashimoto, Yu; Mori, Kenichirou; Ninomiya, Tomoyuki; Suzuki, Seiyuu; Shibata, Naozumi; Murakami, Hidehiro; et al.
Abstract : INTRODUCTION: Monocytes play an important role in innate immunity. Some epidemiological evidence indicates an association between peripheral blood monocytes and ulcerative colitis (UC). The association between peripheral blood monocytes and mucosal healing (MH), however, remains unclear. We evaluated this issue in patients with UC. METHODS: Study subjects consisted of 272 Japanese patients with UC. Monocyte counts were taken in the morning after overnight fasting. Monocyte count was divided into tertiles based on the distribution of values among all study subjects. Information on clinical remission was obtained from medical records. MH was assessed using the Mayo endoscopic subscore. RESULTS: The mean monocyte count was 360.1 ± 155.3/mm 3 . Rates of clinical remission, MH, and complete MH were 61.0%, 66.2%, and 27.9%, respectively. High monocyte count was significantly inversely associated with clinical remission, MH, and complete MH (adjusted odds ratio [OR] 0.45 [95% confidence interval [CI]: 0.23–0.89], OR 0.45 [95% CI: 0.23–0.89], and OR 0.48 [95% CI: 0.23–0.97], respectively). Patients were also classified according to C-reactive protein (CRP) levels; in the low CRP group (<0.1 mg/dL), high monocyte count was independently inversely associated with complete MH but not with clinical remission or MH (OR 0.33 [95% CI: 0.10–0.92], P for trend = 0.027). In the high CRP group, there was no association between monocyte count and clinical outcomes. DISCUSSION: Our findings suggest that peripheral blood monocyte count can be used as a serum supplemental marker for MH in UC patients with low CRP levels.